Well-posed linear systems - A survey with emphasis on conservative systems - Weiss, George; Staffans, Olof J.; Tucsnak, Marius (Zielona Góra: Uniwersytet Zielonogórski)
We survey the literature on well-posed linear systems, which has been an area of rapid development in recent years. We examine the particular subclass of conservative systems and its connections to scattering theory. We study some transformations of well-posed systems, namely duality and time-flow inversion, and their effect on the transfer function and the generating operators.
Keywords: well-posed linear system; regular linear system; operator semigroup; conservative system; scattering theory; time-flow-inversion; differential equations in Hilbert space; beam equation